Bangladeshi migration across the globe: The recent experiences of development and challenges - Sheikh Mohammad Maniruzzaman, Al Masud; Rohana, Hamzah; Hasan, Ahmad (Sryahwa Publication, 2019)
In Bangladesh, international migration has long been crucial to development as it has enormous impacts on creating employment, reducing poverty and ensuring stability to foreign Exchange reserve. It has a significant effect on country’s GDP. Migration and remittances not only maximise income but also minimise risk. International migration outperforms foreign aid and foreign direct investment (FDI) in the development of Bangladesh. Bangladeshi immigrants and their sending remittances are being considered major contributors to develop the country’s economy. Nevertheless, expatriate workers are facing new challenges in KSA, UAE and Malaysia, the traditional job market for Bangladeshi labour migrants. Moreover, there are some irregular migration, mainly taking place in south-east Asian regions and EU member countries affecting the country’s image severely. Along with these experiences, the government should be more pro- active to deal with the issue properly and to develop a national strategy to integrate migration in development planning.